Leaf Growth of Angsana Plants on Reclaimed Land After Coal Mining - Nutayla, Nazula; Rejo, Amin; Adhiguna, Rizky Tirta (Sriwijaya Journal of Environment, 2023)
The majority of coal mining is done using open pit mining techniques, which have an effect and present a challenge to changes in the chemical, physical, and biological characteristics of the soil. Restoration of ecosystems damaged by mining activities is prioritized through revegetation of reclaimed land. The purpose of this study is to evaluate how well Angsana plants develop faster in coal mining reclamation zones when they are planted directly. Field data and observations are utilized to assess the growth of plants that are directly planted in land reclaimed after mining activities. The growth parameters that are observed involve counting the number of leaves for plants using both seedlings and stem-cutting planting materials. The results showed that the average leaf growth in seedling planting material treated with bokashi fertilizer exhibited normal growth with more leaf characteristics compared to the control treatment. However, during the period of 2 to 4 weeks after planting, abscission occurred in leaf growth. The growth in the number of leaves on the seedling planting material was observed from 6 weeks after planting until the end of the study. Meanwhile, the average leaf growth on the planting material of cuttings occurred from 4 weeks after planting to 12 weeks after planting. However, slow leaf growth was noted in the planting material of cuttings treated with coal fertilizer at a dose of 1 kg/planting hole, where leaf growth occurred 11 weeks after planting.